DAMPAK KEBIJAKAN PEMBANGUNAN KARAKTER BANGSA TERHADAP SISWA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 7 SEMARANG - Rizki Dwiarti Ratna Pratiwi; Sri Suwitri; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Issues regarding the education and growth process of children into a very complex social problems. This study aimed to describe the implementation of development policies national character in the SMKN 7 Semarang and impacts arising from the implementation. Design of this research is qualitative descriptive. The results showed that the integration of the values of the foundation of the nation's character has been pretty well according to indicators of class and school.